1991
DOI: 10.1037/0735-7036.105.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of feeding lateralization in the small-eared bushbaby (Otolemur garnettii): A comparison with the ring-tailed lemur (Lemur catta).

Abstract: Feeding related lateralization was examined in a population of 23 small-eared bushbabies (Otolemur garnettii). The three measures used to determine lateralization were food reaching, holding, and manipulation. Sex and age differences were found, with adult females showing a strong right bias and adult males a left bias. Juvenile males were weakly lateralized and less consistent across measures than adult animals. The use of standard scores to assess lateralization allowed species comparisons to be made. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 19 publications
5
30
1
Order By: Relevance
“…If this is true, then the strength of laterality should increase with age-at least among younger animals. This trend has been shown for some other prosimians (Ward et al 1990;Milliken et al 1991). Feistner et al (1994) indeed suggested that this was also the case for the aye-ayes they studied, with only the youngest of these captive animals, Fred (10 months old), showing ambipreference in all measures and the other three juveniles and subadults (Zaza, Sambany, and Annabellee) showing hand preference in at least one measure.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…If this is true, then the strength of laterality should increase with age-at least among younger animals. This trend has been shown for some other prosimians (Ward et al 1990;Milliken et al 1991). Feistner et al (1994) indeed suggested that this was also the case for the aye-ayes they studied, with only the youngest of these captive animals, Fred (10 months old), showing ambipreference in all measures and the other three juveniles and subadults (Zaza, Sambany, and Annabellee) showing hand preference in at least one measure.…”
Section: Discussionmentioning
confidence: 56%
“…The strength of laterality but also the proportion of animals that show the right-hand bias may increase with age (Ward et al 1990). A predominantly right-hand preference is sometimes found in females (Milliken et al 1991;Dodson et al 1992) and possibly in old animals ).…”
Section: Introductionmentioning
confidence: 96%
“…Several studies using a variety of primate species have shown that hand preference may vary as a function of age (WESTERGAARD • SUOMI, 1993;HOPKINS & BARD, 1993), sex (WARD et al, 1990;MILLIKEN et al, 1991), task complexity (FAGOT & VAUCLAIR, 1991;HELMS TILLERY et al, 1995), posture (FoRSYTHE et al, 1988;RONEY & KING, 1993;HOPKINS, 1993;DEVLEESCHOUWER et al, 1995), or of whether the hand use is visually or tactually guided VAUCLAIR & FAGOT, 1987).…”
Section: Introductionmentioning
confidence: 95%
“…In comparison, Prosimii (lemuriforms and lorisiforms) are thought to be less variable in grip posture, to show no digital individualization and to use the mouth for grasping more often [Bishop, 1964]. In order to grasp static foods, the lemuriforms appear to prefer to grasp with the mouth as shown both by observations in the wild [Petter, 1962] and studies on manual preference [Larson et al, 1989;Ward et al, 1990;Milliken et al, 1991a;Dodson et al, 1992;Ward and Hopkins, 1993;Ward, 1995;Leliveld et al, 2008;Nelson et al, 2009;Scheumann et al, 2011]. However, these studies on manual preference often adopted protocols forcing the subjects to take static food through a wire mesh or a slot with their hand.…”
Section: Introductionmentioning
confidence: 99%